Factors Effecting Students’ Academic Performance (A study of BZU, Multan): Factors Effecting Students’ Academic Performance - raza, ali (Journal of Peace, Development and Communication, 2022)
Education institution has always emphasis on its student’s performance. Pupil’s educational success is part of the concern for high-level education different studies are conducted to evaluate different causes which affect student’s academic results. The study is an effort to understand the factors that determine the performance of students. It was quantitative research in nature the objectives of this study are some factors like learning facilities, students’ interest, and peer group effect BS and Master students performance at BZU, Multan. The sample for the study consists of 201 students from one-third of departments of social sciences by using multi-stage sampling and questionnaires as a tool for data collection. Data was analyzed through SPSS and Linear regression to find out the important relationship between variables. The result revealed that learning facility and student’s interest has an impact on the students’ academic performance but peer group has no impact on students’ academic performance. Future research is needed to investigate other factors like student personality factors, home background, institutional and friends’ agents.